Impact of Excess Weight Gain on Risk of Postpartum Infection in Class III Obesity - Courtney J. Mitchell; LaMani Adkins; Ann Tucker; Haywood Brown; Anne Siegel; Sarah Dotter-Katz (Thieme Medical Publishers, Inc., 2020)
Objective To assess the impact of gestational weight gain >20 pounds (more than Institute of Medicine [IOM] recommendations) on postpartum infectious morbidity in women with class III obesity. Methods This is a retrospective cohort of term, nonanomalous singleton pregnancies with body mass index ≥40 at a single institution from 2013 to 2017. Pregnancies with multiple gestation, late entry to care, and missing weight gain data are excluded. Primary outcome is a composite of postpartum infection (endometritis, urinary tract, respiratory, and wound infection). Secondary outcomes include components of composite, wound complication, readmission, and blood transfusion. Bivariate statistics compared demographics, pregnancy complications, and delivery characteristics of women exceeding IOM guidelines (GT20) with those who did not (LT20). Regression models were used to estimate adjusted odds of outcomes. Results Of 374 women, 144 (39%) gained GT20 and 230 (62%) gained LT20. Primiparous, nonsmokers more likely gained GT20 (p < 0.05). No significant difference in other demographics. Among women who gained GT20, 10.4% had postpartum infectious morbidity compared with 3.0% in LT20 (p < 0.01). Wound infection is more common in the GT20 group (7.6 vs. 2%, p = 0.02). After adjustment, women who gained GT20 had threefold higher odds of postpartum infectious morbidity (adjusted odds ratio: 3.17, 95% confidence interval: 1.17, 8.60). Conclusion Women with class III obesity who gain more than the IOM recommends are at increased risk for postpartum infectious morbidity.